Esthetic improvement of white spot lesions and non-pitted fluorosis using resin infiltration technique: Series of four clinical cases - Neeraj Gugnani; I K Pandit; Virinder Goyal; Shalini Gugnani; Jyoti Sharma; Shikha Dogra (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2014)
White opacities have always been a major concern of esthetics for patients and can have varying etiology. In general, white discolorations of enamel might be due to dental fluorosis, early caries (white spot lesions), developmental defects etc. Conventional treatment options available for such opacities include non-invasive and invasive approaches. Recently, a new "micro-invasive" technique has been introduced as an alternative therapeutic approach that improves such opacities esthetically, in a single sitting, is painless and exhibits no complications. This case series illustrates the use of resin infiltration to treat fluorosis stains and WSLs, exhibiting significant improvement in esthetics.